2016
DOI: 10.1080/23809000.2016.1191948
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology and management of radiotherapy-induced fatigue

Abstract: Fatigue is one of the most common side-effects accompanying radiotherapy, but arguably the least understood. Radiotherapy-induced fatigue (RIF) is a clinical subtype of cancer treatment-related fatigue. It is described as a pervasive, subjective sense of tiredness persisting over time, interferes with activities of daily living, and is not relieved by adequate rest or sleep. RIF is one of the early side-effects and long-lasting for cancer patients treated with localized radiation. Although the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 82 publications
0
34
0
1
Order By: Relevance
“…In this sense, one can note that the etiology of the symptom is complex, and can be linked not only to the intensity of the radiation received, but also to the consequence of alterations at a cellular level, especially at signaling ways in the tumor microenvironment, as in the exacerbated release of pro-inflammatory cytokines and chemokines, for example 29-30 . Thus, the inflammatory process resulting from radiation therapy may also be one of the possible causes of fatigue 25 , besides issues involving the psychological state, as stress and nutritional changes 8-9,29-30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, one can note that the etiology of the symptom is complex, and can be linked not only to the intensity of the radiation received, but also to the consequence of alterations at a cellular level, especially at signaling ways in the tumor microenvironment, as in the exacerbated release of pro-inflammatory cytokines and chemokines, for example 29-30 . Thus, the inflammatory process resulting from radiation therapy may also be one of the possible causes of fatigue 25 , besides issues involving the psychological state, as stress and nutritional changes 8-9,29-30 .…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is one of the most cited symptoms in the literature when considering cancer patients, and is also one of the most common side effects accompanying radiation therapy 9 . It affects from 50% to 90% of HNC patients undergoing radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…From that review, it was concluded that clustering of CRS is linked with immune and inflammatory pathways (Lynch Kelly et al, ). Another review on the etiology of radiation‐induced fatigue highlighted the multi‐mechanism pathobiology of radiation‐induced fatigue, including genetic, metabolic, immune, and inflammatory processes (Hsiao, Daly, & Saligan, ). Several reviews from CRS consortium members are ongoing, including an integrative review on the effects of alternative interventions (i.e., exercise, mindfulness‐based cognitive therapy, auricular point acupressure) on CRS.…”
Section: Research Exemplars and Outcomes Of The Crs Consortiummentioning
confidence: 99%
“…With fractionated doses of radiation for cancer treatment, radiation-induced fatigue sets in within a few days after start of treatment and decreases after treatment completion [ 7 ]. Although the underlying mechanisms of fatigue have been studied under several disease conditions, an understanding of the etiology, mechanisms, and risk factors of radiation-induced fatigue remains elusive, and this symptom remains poorly managed [ 8 , 9 , 10 ]. Investigating initial radiation-related behavioral changes by using animals might provide important information to aid understanding of the health effects of radiation exposure and clinical features of radiation injury.…”
Section: Introductionmentioning
confidence: 99%